Landasan Pendidikan Qur’ani - Maryam Ismail (Jurnal Ilmiah Islamic Resources, 2022)
Basically, the concept of education in Islam already has guidance both in the Qur'an and Hadith. The Prophet saw as the messenger of Allah SWT is enough to provide learning and examples for education and how to apply it. So far, education is dominated by theories of knowledge and takes educational patterns that come from outside views which may not necessarily contribute to Islamic education. Meanwhile, the educational foundation in the Qur'an which is sourced from Allah's instructions and described by Muhammad saw is ignored and is more interested in using western education patterns that are liberal and secular. Exploration of the content of the Qur'an resulted in a theory called Qur'anic education which applies the basic ideas of the Qur'an and Sunnah in a realistic form. and filters for Islamic educators to continue to exist and istiqamah in carrying out Islamic education patterns and not being carried away by the currents of knowledge education theories alone